Organizational resilience: proposition for an integrated model and research agenda - Goldschmidt,Cristina Chaves (2019)
This theoretical essay is aimed at shedding light on and synthesizing the concepts of resilience in relation to employees and organizations and proposing an integrated analysis model that gives rise to a research agenda embracing methodological aspects and thematic connections, which might contribute to a debate on the construct that involves differentiated levels of analysis. Accordingly, a historic review of the constructs discussion and its specificities will be presented, including the following organizational resilience concepts: the procedural, dynamic, and ecosystemic capacity activated by people (individual resilience) and processes (systemic resilience) in the face of adversity, the generation of a response that allows the recovery of balance, and the performance of healthy adaptation through the activation of elements, in the subjective or internal and objective or external plans, which might be reinforced or renewed during the process, thus ensuring the sustainability of the resilient result and/or the expansion of resilience capacity.